PENDIDIKAN KEAGAMAAN DI PESANTREN SALAF (Pembelaan terhadap Fikih-Sufistik Model al-Imam al-Ghazali) - Suteja, Suteja (Paedagogia: Jurnal Pendidikan, 2017)
Pesantren as an educational institution and center of the spread of Islam is born and developed since the beginning of the arrival of Islam in the archipelago. This institution stood for the first time in the days of Walisongo. Sufism is part of the Islamic teachings of the easiest and quickly adapt to the traditions and even the mystique of the local community. Significant influential figures include: al-Ghazali who has described the moderate concept of tasawuf akhlaqi accepted in all circles of the fuqaha ', Ibn' Arabi, as his work strongly influences the teachings of almost all Sufis, as well as the founders of the tarekat such as' Abd. al-Qadir al-Jaylani whose teachings form the basis of the Qadiriyah congregation, Abu al-Najib al-Suhrawardi, Najmudddin al-Kubra whose teachings were very influential on the tarkeat of Naqsyabandiyah, al-Hasan al-Syadzali Sufis African origin and founder of the tarekat Syadzaliyah, Bahauddin al -Bukhari al-Naqsyabandi, and 'Abdullah al-Shattar. And the above mentioned Sufism method developed is the continuity of Sufism of al-Ghazali.